A duckling is born - Isenbart, Hans-Heinrich, 1923-; Baumli, Othmar, 1936- (New York : Putnam, 1981)
Follows the development of a mallard duckling from the mating of his parents to his first swim, less than an hour after birth.
Translation of: Ein Entchen kommt zur Welt.
Notable/Best Books (A.L.A.).
School Library Journal.
Booklist.
4.2
K-3
Keywords: Mallard -- Juvenile literature; Embryology -- Birds -- Juvenile literature; Animals -- Infancy -- Juvenile literature; Mallard; Ducks; Animals -- Infancy; Mallard; Ducks; Animal babies; Mallard; Animals -- Infancy; Ducks